C-Rate Capability of Ion-Beam Sputter Deposited Silicon, Carbon and Silicon/Carbon Multilayer Thin Films for Li-Ion Batteries. Issue 8 (1st August 2022) - Hüger, Erwin; Jin, Chao; Uxa, Daniel; Schmidt, Harald
Abstract : Silicon is highly desired as high-energy density active Li storage material in Li-ion batteries, but usually does not withstand extended cycling. This work examines the C-rate capability up to Li plating and the long term cycling for ion-beam sputter-deposited amorphous (Si/C) × 10 multilayers (MLs) (with individual layer thicknesses between 5 and 27 nm), as well as for amorphous silicon and carbon single layers (with film thicknesses between 14 and 230 nm). Differential capacity plots were analyzed to examine the lithiation and delithiation mechanism. The silicon single-layers are stable for the first five cycles only, with a behavior of thinner films similar to supercapacitors. The carbon single layers show good cycling stability but also low capacities similar to graphite. The combination of silicon and carbon within Si/C MLs improved capacity and cycling behavior. The Li + insertion and extraction process from the Si/C MLs is reversible and dominated by silicon. It coincides even at high currents (10C) and after hundreds of cycles with that of the thicker silicon film at its initial cycles. The MLs combine the positive property of carbon (reversible cycling) and of silicon (high capacity). Thinner carbon layers in the ML increase the silicon capacity for all cycles. The topic of irreversible Li-losses is discussed.